Analisis Penanaman Karakter Tanggung Jawab Pada Siswa Kelas V SDN Tapos 03 - Nani Mariyani; Dadang Kurnia; Ade Wijaya (STKIP Andi Matappa Pangkep, 2022)
The planting of responsible character education is carried out in class V of SDN Tapos 03, Tenjolaya District, Bogor Regency, Even Semester of the 2021/2022 Academic Year. The research method used in this study is a qualitative method with a descriptive approach which intends to understand the phenomenon of what is experienced by the research subject. From the results of observations, interviews and the distribution of questionnaires in schools, it can be concluded that the instilling of the character of responsibility instilled by teachers in students is very important. goodteacher's example is needed as an effort to instill the character of student responsibility in schools, teachers instill the character of responsibility through habituation and approaches to students in the learning process at school directly. the analysis of the cultivation of the character of responsibility in the fifth grade students of SDN Tapos 03 District of Tenjolaya, Bogor Regency of the Academic Year 2021/2022 can be carried out well by the teacher, the cultivation of the character of responsibility can be done through activities learning, student activities outside of learning and routine activities or through habituation which is applied as a routine class program.